2008
DOI: 10.1159/000156485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cannabinoid Receptor Agonists on Streptozotocin-Induced Hyperalgesia in Diabetic Neuropathy

Abstract: The effect of CB-1 and CB-2 receptor agonists, as well as an influence of a non-selective inhibitor of nitric oxide synthase (NOS), L-NOArg, and an inhibitor acting preferentially on cyclooxygenase-1 (COX-1), indomethacin, on the action of cannabinoid receptor agonists in a streptozotocin (STZ)-induced neuropathic model was investigated. When administered alone, a non-selective cannabinoid receptor agonist, WIN 55,212-2, a potentially selective CB-1 cannabinoid receptor agonist, Met-F-AEA, and a selective CB-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…The beneficial effect of AM1241 in a preclinical model of DN makes CB2 agonism an attractive new strategy for the treatment of DN. CB2 activation may also positively affect other diabetes-related complications as CB2 agonists may, under certain conditions, delay progression of atherosclerotic lesions (14) and ameliorate diabetes-induced neuropathic pain (46,47) in rodents. The observation that CB2 receptors are also expressed by podocytes of human origin and undergo downregulation in patients with advanced DN suggests that our results may also have clinical relevance in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of AM1241 in a preclinical model of DN makes CB2 agonism an attractive new strategy for the treatment of DN. CB2 activation may also positively affect other diabetes-related complications as CB2 agonists may, under certain conditions, delay progression of atherosclerotic lesions (14) and ameliorate diabetes-induced neuropathic pain (46,47) in rodents. The observation that CB2 receptors are also expressed by podocytes of human origin and undergo downregulation in patients with advanced DN suggests that our results may also have clinical relevance in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking CB1 function has been presented as an effective means of alleviating both hyperglycaemia and dyslipidemia at several levels . Recent studies have also suggested a possible role for CB1 and CB2 in various diabetic complications, such as diabetic cardiovascular dysfunction, nephropathy and neuropathy, particularly highlighting the mechanisms beyond the metabolic consequences of the activation of the endocannabinoid system .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that THC (Williams et al, 2008) and WIN55,212-2 (Bujalska, 2008;Doğrul et al, 2004;Ikeda et al, 2013;Jahanabadi et al, 2016;Mohammadi-Farani et al, 2010;Ulugol et al, 2004;Vera et al, 2012;Vincenzi et al, 2013) produce antinociception in rodent STZinduced peripheral neuropathy. In particular, either single or repeated administration of WIN55,212-2 or AM1241, dosedependently attenuated STZ-induced hyperalgesia (Bujalska, 2008). Furthermore, repeated administration for 1 month of medium or high doses of intranasal WIN55,212-2 improved thermal hyperalgesia and mechanical allodynia in STZtreated mice (Toth et al, 2010).…”
Section: Streptozotocin-induced Diabetesmentioning
confidence: 99%